Adult-onset celiac disease for the primary care physician. Issue 3 (1st October 2017) - Naidoo, Kamil; McCrossan, Laura
Abstract : Celiac disease is a common autoimmune condition with a prevalence of 1%–2%. In recent years there has been a paradigm shift in management from tertiary care into the community. With a wide array of manifestations, including nonspecific and extraintestinal symptoms, this disorder can be difficult to diagnose, prolonging morbidity for patients. This review article aims to augment the primary physician's knowledge of the common presentation, diagnosis, management, and follow-up of this disease.